Consumer Information Search Behavior for Experiential and Material Purchases - Aydin, Asli Elif (Journal of Economics and Behavioral Studies, 2014)
The objective of this study is to determine whether sources of information consulted and the extent of information search differ between experiential and material purchases. For this purpose two experimental studies were conducted. It is demonstrated that moving along the experiential-material purchase continuum; consumers’ reliance on personal sources, especially personal independent sources intensifies towards experiential purchase pole and decreases towards material purchase pole. In addition, for material purchases; direct observation is preferred more compared to personal sources of information. Finally, it is revealed that the total amount of search is greater for experiential purchases than material purchases. The results suggest that experiential and material purchases require different types of search conduct due to their distinct natures.